Development of methods of determination of technological houses 3,5-dinitro- and 3,5-diaminobenzoics acids at synthesis of sodium amidotrіzоate - T. A. Palchevska; O. P. Baula; V. I. Bessarabov; K. V. Palchevskyі (The State Expert Center of the Ministry of Health of Ukraine, 2019)
Ionogenic contrast preparations, Triombrast, Urographin and Trasograph containing the active pharmaceutical ingredient (APhI), sodium amidotrizoate, have a positive experience in medical diagnosis. Qualitative control of intermediate products of each stage of AFI to prevent the possibility of technological toxic impurities - a mixture of 3,5-dinitro- and 3,5-diaminobenzoic acids (3,5-dNBK and 3,5-dABK) in the composition of the target product for safety X-ray contrast drugs in their application is a pressing issue today. The aim of the work - to develop a method for determining the technological impurities of 3,5-dNBK and 3,5-dABK acids in the synthesis of amidotrizoate sodium using UV spectrophotometry, which will allow to determine these impurities without their preliminary separation both in the inter-operative process control and in the finished product. The objects of study are aqueous solutions of 3,5-dNBK and 3,5-dABK acids, as well as their binary mixtures. The absorption spectra of the analytes were recorded using a Specord UV VIS spectrophotometer in the ultraviolet region. Calculations of the concentrations of the investigated acids in the composition of their binary compositions were performed according to the Vierordt's method. It is found that the absorption maxima of aqueous solutions of 3,5-dNBK and 3,5-dABK are at wavelengths of 240 nm and 218 nm; in the experimental conditions, the molar absorption coefficient for 3,5-dinitrobenzoic acid was the same (e1240 = e1218) and was equal to 17 940 ± 150. For solutions of 3,5-diaminobenzoic acid, the molar absorption coefficients were different: for a wavelength of 218 nm, the molar e2218 = 28 890 ± 220 and at a wavelength of 240 nm e2240 = 10 770 ± 80. Based on the Firordt method, taking into account the molar absorption coefficients of the investigated acids, we determined mathematical formulas for the quantitative analysis of the composition of mixtures at different ratios of analytes within their total concentration 1-6·10-5 M. Spectrophotometric Vierordt's method of quantitative analysis of 3,5-dinitro- and 3,5-diaminobenzoic acids, as well as their binary mixtures in aqueous solutions can be applied in the industrial production of iodine-containing contrast agents, where in the first stages of synthesis, the corresponding nitrobenzoic acid is reduced. Strict control of the possible amount of impurities in the first stage of synthesis of sodium amidotrizoate - the main active ingredient of ionic iodine-containing X-ray contrast drugs (Triombrast, Urografin, Trasograph) - will improve the quality of the final product and will allow to reduce the final product.